2007
DOI: 10.1038/sj.ijo.0803686
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and weight change since 20 years of age and risk of coronary heart disease among Japanese: the Japan Public Health Center-Based Study

Abstract: Background: Obesity and weight gain are associated with increased risk of coronary heart disease in Western countries. However, their impact is not well elucidated in Asia, where body mass index (BMI) levels are generally lower than in Western countries. We examined associations of BMI (kg/m 2 ) and weight change with risk of coronary heart disease in Japanese people. Methods and results: A total of 43 235 men and 47 444 women aged 40-69 years living in communities were followed up from 1990 to 2001 in the Jap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 35 publications
2
57
1
1
Order By: Relevance
“…A recent 10-year follow-up study of Japanese subjects reported that weight gain of X10 kg among men with BMI o21.7 at age 20 was associated with a doubling of the risk of coronary heart disease but that no excessive risk was established for men with BMI X21.7. 19 We also found that the prevalence of excessive daytime sleepiness was elevated for BMI X30 and for BMI gain of X3 Abbreviations: BMI, body mass index; OR, odds ratio; RDI, respiratory disturbance index. Multivariable adjustment variables are shown in Table 2 and further for BMI (kg m À2 ) at 20 years of age.…”
Section: Discussionmentioning
confidence: 61%
“…A recent 10-year follow-up study of Japanese subjects reported that weight gain of X10 kg among men with BMI o21.7 at age 20 was associated with a doubling of the risk of coronary heart disease but that no excessive risk was established for men with BMI X21.7. 19 We also found that the prevalence of excessive daytime sleepiness was elevated for BMI X30 and for BMI gain of X3 Abbreviations: BMI, body mass index; OR, odds ratio; RDI, respiratory disturbance index. Multivariable adjustment variables are shown in Table 2 and further for BMI (kg m À2 ) at 20 years of age.…”
Section: Discussionmentioning
confidence: 61%
“…19 It is of value to examine the criteria of the metabolic syndrome that effectively predict the risk of cardiovascular disease among lessobese populations, such as the Japanese. 20 We examined the contribution of the metabolic syndrome and its components to the incidence of ischemic heart disease and stroke among Japanese men and women, among whom there is a low prevalence of obesity.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 A 10-year follow-up study of Japanese subjects reported that men who have weight gain since the age of 20 have a 1.4-fold higher risk of CAD than those with no weight change. 4 In contrast, several clinical studies showed that patients with cardiovascular disease or overweight with coronary risk factors who lost weight intentionally had decreased risk of CAD: the HRs were 0.57 (0.39-0.84) and 0.62 (0.42-0.92). 19,20 No previous prospective studies, however, have examined the association between weight change and risk of HF in the general population.…”
Section: Resultsmentioning
confidence: 94%